2019
DOI: 10.1177/1942775119858655
|View full text |Cite
|
Sign up to set email alerts
|

Microaggressions in Administrator Preparation Programs: How Black Female Participants Experienced Discussions of Identity, Discrimination, and Leadership

Abstract: Using Sue et al.’s microaggressions framework, this qualitative study focused on the preparation experiences of 10 Black, female school leaders to examine how and in what ways identity, leadership, and discrimination were discussed in their administration preparation programs. We find participants were neither given space to explore their identities or experiences of discrimination nor did they learn strategies to address them. Instead, leadership was treated as an identity-neutral endeavor, and conversations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 95 publications
0
7
0
1
Order By: Relevance
“…However, there are still gaps in Latin America, specifically in Colombia, where women, despite being resilient and covering some senior management positions, still have little presence in the system. Some studies claim that when women cover management positions it is possible to increase the diversity of perspectives and opinions in companies [20,22]. According to the official World Bank data, in Colombia in the last 10 years the women labor participation rate (% of the female population between 15-64 years old) has been equal to 43.39%, with only the 20% covering top management positions (see Figure 1).…”
Section: Resilient Female Leadership and Its Distinctive Approach To ...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are still gaps in Latin America, specifically in Colombia, where women, despite being resilient and covering some senior management positions, still have little presence in the system. Some studies claim that when women cover management positions it is possible to increase the diversity of perspectives and opinions in companies [20,22]. According to the official World Bank data, in Colombia in the last 10 years the women labor participation rate (% of the female population between 15-64 years old) has been equal to 43.39%, with only the 20% covering top management positions (see Figure 1).…”
Section: Resilient Female Leadership and Its Distinctive Approach To ...mentioning
confidence: 99%
“…• Hypothesis 1 (H1 We investigated how different stakeholder perspectives need to be combined [22]. The focus is on how a company can create competitive advantage and on how human and organizational factors are able to influence this epochal change.…”
Section: Introductionmentioning
confidence: 99%
“…The study also allowed to identify the main characteristics, skills and leadership styles of female leaders. In this way, it is possible to define a profile of sustainable women leaders with the following traits: thinking systematically/holistically, managing complexity, and inclusive approach to leadership (Weiner et al, 2019;Acevedo-Duque et al, 2021;Kadi-Montiel and Acevedo-Duque, 2021). In addition, it was found that the main actions implemented by the women leaders surveyed are waste of energy, water and raw materials and proper waste management with regard to the environmental dimension (Quisumbing et al, 2001;Nightingale, 2011), employee communication/dialogue activities, corporate welfare projects and promotion of local employment with respect to the social component (Galletta et al, 2022).…”
Section: Conclusion and Limitationsmentioning
confidence: 99%
“…Furthermore, women have unique leadership approaches to build trust among workers, focus on conflict resolution and facilitate collaboration (Westermann et al, 2005;Eagly and Carli, 2007), while men tend to adopt a dominant leadership style. Thus, women managers foster a diversity of perspectives and opinions (Weiner et al, 2019;Kadi-Montiel and Acevedo-Duque, 2021). Additionally, female leadership is characterized by an enterprising spirit, a capacity to build work teams, and the ability to make decisions in times of crisis (Acevedo-Duque et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Es por esto que, desde hace varios años se estudia el capital humano como el conjunto de conocimientos de cada trabajador que sirven para desempeñar sus actividades diarias (Weiner et al, 2019). En esta investigación se muestra al capital humano hondureño como gente trabajadora y resiliente, ya que son capaces de adaptarse y superar los cambios que surgen de las crisis económicas, sociales y políticas que puedan afectar las organizaciones.…”
Section: Capital Humano Resiliente En La Industria Manufacturera Inte...unclassified